Pengaruh Desain Produk, Harga, Etika Bisnis Islam, dan Kualitas Produk terhadap Keputusan Pembelian Kopi Robusta Home Industry di Kecamatan Jangkat - Angga Rizki Prawira; Hesi Eka Puteri (Jurnal Multidisiplin Indonesia, 2026)
This study is a field research project employing a descriptive quantitative approach. Data sources comprised primary data obtained directly from respondents via structured questionnaires, alongside secondary data supporting the theoretical framework and the research area's context. Moderated Regression Analysis (MRA) was utilized as the analytical method using SmartPLS software, with a sample size of 194 respondents consisting of consumers of home-industry Robusta coffee. Partial testing (t-test) results indicated that only Product Quality exerted a positive and significant influence on Purchase Decisions, whereas Product Design, Price, and Islamic Business Ethics did not demonstrate a significant partial linear effect. However, the simultaneous F-test results revealed that all independent variables collectively exerted a significant influence on Purchase Decisions, with a contribution value (Adjusted R-Square) of 36.8%. Meanwhile, the moderation test (MRA) results disclosed that Consumer Experience (Z) significantly moderated the influence of Price on Purchase Decisions, acting to weaken that relationship (negative moderation). Conversely, Consumer Experience did not moderate the influence of the other independent variables on Purchase Decisions. The study's implications suggest that business operators should maintain consistent coffee flavor quality and provide product education to foster positive consumer experiences.